Chronic pain and depression. Correlation and treatment - A review of current literature - Barbara Wołoszyn; Patrycja Rzeźnik; Maciej Sobczyk; Weronika Stachera; Julia Guzowska; Aleksandra Chajnowska; Aleksandra Borowy; Wiktoria Suchcicka; Małgorzata Zach; Julia Stępień (Quality in Sport, 2025)
Introduction and purpose